Long-term hypoxia increases calcium affinity of BK channels in ovine fetal and adult cerebral artery smooth muscle - Tao, Xiaoxiao (Am J Physiol Heart Circ Physiol, 2015)
Acclimatization to high-altitude, long-term hypoxia (LTH) reportedly alters cerebral artery contraction-relaxation responses associated with changes in K(+) channel activity. We hypothesized that to maintain oxygenation during LTH, basilar arteries (BA) in the ovine adult and near-term fetus would show increased large-conductance Ca(2+) activated potassium (BK) channel activity. We measured BK channel activity, expression, and cell surface distribution by use of patch-clamp electrophysiology, flow cytometry, and confocal microscopy, respectively, in myocytes from normoxic control and LTH adult and near-term fetus BA. Electrophysiological data showed that BK channels in LTH myocytes exhibited 1) lowered Ca(2+) set points, 2) left-shifted activation voltages, and 3) longer dwell times. BK channels in LTH myocytes also appeared to be more dephosphorylated. These differences collectively make LTH BK channels more sensitive to activation. Studies using flow cytometry showed that the LTH fetus exhibited increased BK β(1) subunit surface expression. In addition, in both fetal groups confocal microscopy revealed increased BK channel clustering and colocalization to myocyte lipid rafts. We conclude that increased BK channel activity in LTH BA occurred in association with increased channel affinity for Ca(2+) and left-shifted voltage activation. Increased cerebrovascular BK channel activity may be a mechanism by which LTH adult and near-term fetal sheep can acclimatize to long-term high altitude hypoxia. Our findings suggest that increasing BK channel activity in cerebral myocytes may be a therapeutic target to ameliorate the adverse effects of high altitude in adults or of intrauterine hypoxia in the fetus.